Phytochemical Screening and Antimicrobial Activities of Some Selected Medicinal Plants of Nepal - Rajendra Gyawali, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Phytochemical Screening and Antimicrobial Activities of Some Selected Medicinal Plants of Nepal